Atypical presentation of abdominal pain and fever in positive patient for COVID19. Case report and literature review - González Arias, Mauricio (2020)
The clinical case of a 38-year-old female patient, seen in an emergency room in a New York hospital, who consults for abdominal pain, fever and fatigue is presented. Complementary studies show lymphopenia and slight alteration of transaminases. Abdominopelvic CT scan visualizes images in the lung bases, reticulonodular type. A sample was taken for COVID-19. She was managed in emergencies with parenteral hydration, antipyretics, oral antibiotics are indicated and social isolation measures are instructed. Two days later, it cost again, confirming positive COVID-19. It is followed on an outpatient basis, one week later with good clinical evolution. Additionally, a clinical review and pathophysiological explanation of the involvement of the digestive tract by the virus and the atypical form of presentation with abdominal pain are shown.